MicroRNA-494 augments fibrotic transformation of human retinal pigment epithelial cells and targets p27 with cell-type specificity - Leng, Theodore; Kamboj, Georgia; Sun, Xiaoyun; Chang, Heather; Davda, Prisha; Greer, Majesty; Stary, Creed M. (Frontiers in Ophthalmology, 2023)
Epiretinal membranes (ERMs) are the result of fibro-cellular proliferation that cause distortion and impairment of central vision. We hypothesized that select microRNAs (miRs) regulate retinal fibro-proliferation and ERM formation. Following IRB approval, a pilot study was performed in patients presenting for retina surgery with and without clinical ERMs. Total RNA was isolated from ERM tissue and controls from non-ERM vitreous and subjected to miR profiling via microarray analysis. MiR-494 was identified as the only miR selectively expressed at significantly greater levels, and in silico analysis identified p27 as a putative fibroproliferative gene target of miR-494. In vitro testing of miR-494 and p27 in fibrotic transformation was assessed in spontaneously immortalized human retinal pigment epithelial (RPE) and human Müller cell lines, stimulated to transform into a fibroproliferative state via transforming growth factor beta (TGFb). Fibroproliferative transformation was characterized by de novo cellular expression of alpha smooth muscle actin (aSMA). In both RPE and Müller cells, both TGFb and miR-494 mimic decreased p27 expression. In parallel experiments, transfection with p27 siRNA augmented TGFb-induced aSMA expression, while only in RPE cells did co-transfection with miR-494 inhibitor decrease aSMA levels. These results demonstrate that miR-494 augments fibrotic transformation in both Müller cells and RPEs, however only in RPEs does miR-494 mediate fibrotic transformation via p27. As p27 is known to regulate cellular proliferation and differentiation, future studies should extend clinical testing of miR-494 and/or p27 as a potential novel non-surgical therapy for ERMs, as well as identify relevant miR-494 targets in Müller cells.